Too Much Familiarity! The Developmental Path of the Fluency Heuristic in Children. Issue 3 (18th August 2020) - Geurten, Marie; Willems, Sylvie; Lloyd, Marianne
Abstract : We tested whether changes in attribution processes could account for the developmental differences observed in how children's use fluency to guide their memory decisions. Children ranging in age from 4 to 9 years studied a list of familiar or unfamiliar cartoon characters. In Experiment 1 ( n = 84), participants completed a recognition test during which the perceptual fluency of some items was enhanced using a prime. In Experiment 2 ( n = 96), participants completed a source recollection judgment on their recognition decisions. Primed items were recognized at a higher rate than unprimed items. However, while young children rely on fluency for all items, older children use fluency only for unfamiliar items. This pattern came together with a reduction in familiarity‐based—but not recollection‐based—memory responses.